Development of bursa of Fabricius in relations to humoral immunity in chicken embryo - KUMAR, RAJESH; SINGH, g k; CHAUHAN, R S (The Indian Journal of Animal Sciences, 2014)
Lymphoblastogenesis assay, using lipopolysaccharide (LPS) as mitogen, revealed blast formation by B-lymphocytes only at 21 5t day but not at the 16th day of incubation. Enzyme linked immunosorbent assay suggested the presence of IgG IgM antibodies at both 16th and 21st day of incubation, indicating the presence of the maternal antibodies in embryonic blood even before the development of the cmbryonic immunity. Hlstoarchitecture of the bursa of Fabricius underwent marked changes during 16th to 21st day of incubation. There was increase in the number of the bursal follicles at 21st day. Follicles were well arranged with a fine network of reticular and collagen fibres around follicles at 21st day. All these changes favoured the production of functional B-lymphocytes by the bursa of Fabricius at 21 day of incubation.